Drivers of Antarctic Sea Ice Volume Change in CMIP5 Models. Issue 11 (7th November 2018) - Schroeter, S.; Hobbs, W.; Bindoff, N. L.; Massom, R.; Matear, R.
Abstract: Antarctic sea ice trends have to date been linked to surface winds, through sea ice motion and atmospheric thermal advection. This paper analyzes sea ice volume in 10 Coupled Model Intercomparison Project Phase 5 (CMIP5) model configurations under pre‐industrial and historical climate forcings, to compare the relative importance of ice motion and thermodynamic processes. We find that the models' responses to historical forcings is dependent on their sea ice motion formulation; models with low‐magnitude sea ice motion tend to have historical trends that are dominated by thermodynamic processes, while sea ice models with higher‐magnitude motion have more spatially variable relative contributions from dynamic and thermodynamic processes. Trends at the sea ice edge during the season of sea ice advance are generally dominated by dynamic processes, whereas during retreat thermodynamic trends dominate. The models show more disagreement in the sea ice interior. This analysis highlights the different estimates and patterns of sea ice volume among global climate models and offers insight into the drivers of sea ice volume change as well as the subsequent implications for simulated atmosphere‐sea ice‐ocean interactions. Plain Language Summary: Increasing observed Antarctic sea ice is thought to be largely driven by surface winds, through driving sea ice motion and advecting warm air southward to melt ice in some regions. However, global climate models do not reproduce observed sea ice trends. This paper analyzes the sea ice volume budget in 10 climate models to see how much simulated sea ice change is driven by dynamic processes such as wind‐driven sea ice motion, and how much is due to thermodynamic freeze and melt processes. We find that the models generally agree when it comes to mean sea ice volume change, with dynamic processes dominating the sea ice edge and thermodynamic processes dominating in the interior of the sea ice pack. However, the models disagree about trends of sea ice volume. In the sea ice interior, each process dominates approximately half the models in all sea ice sectors, and thermodynamic processes tend to dominate in models with low‐magnitude average sea ice motion. These results provide insight into the estimates and patterns of Antarctic sea ice in global climate models, helping to understand the disparity between simulated and observed sea ice trends. Key Points: Thermodynamic drivers tend to dominate trends of Antarctic sea ice volume in models with low‐magnitude mean sea ice mass transport Drivers of sea ice volume trends in models with higher‐magnitude mean sea ice mass transport have large spatial and seasonal variability Biases in mean Antarctic sea ice concentration are unrelated to the dominant processes driving sea ice volume trends